System and method for predicting pure uterine contraction hypodynamia postpartum hemorrhage - QU JIANGXUE; ZENG SHUAI; CHEN LIAN; SHI HUIFENG; JIANG HAI; ZHAO YANGYU (2024)
The invention relates to a system and a method for predicting pure uterine contraction postpartum hemorrhage. The system comprises a detection sample acquisition unit, a detection sample injection unit, a targeted metabolite and protein concentration acquisition unit, a data analysis and risk prediction model construction unit and a judgment standard setting unit. Based on the identified metabolite and protein with significant difference between the groups, performing binomial log2 regression analysis on log2 conversion values of absolute concentrations of the metabolite and protein so as to calculate the morbidity probability of the pure uterine weakness postpartum hemorrhage; absolute concentrations of metabolites and proteins are used as independent variables X, and a logistic regression probability function is P (Y = 1X) = # imgabs0 #; wherein X = [x1, x2, x3] is an independent variable matrix; z = WX + w0; w = [w1, w2, w3] as a weight coefficient matrix; w0 is a constant term; and setting an optimal judg